(untitled) (Global Journal of Human-Social Science, 2015)
Understanding the basic relationships between rainfall and runoff is vital for effective management of flood water The Lawra District of the Upper West Region the driest region in Ghana has experienced periodic and devastating flash floods resulting from high intensity short duration rainfall a characteristic of semi-arid and arid regions However all these go waste leading to lack of water during the long dry season Many methodologies have been applied such as using Digital Elevation Model DEM for hydrological modelling and watershed delineation In this work delineated catchment area computed is used in HEC-HMS for flood volume computation Annual rainfall for 2009 a flood year of 1178 38mm 46 393in gives a runoff of 1 134m 44 652in and a volume of 36 065 515 893m3 However a volume of 31 313 221 5m3 was obtained for August September and October months with heaviest rainfall alone Lumped Hydrological modelling with remote sensing data and GIS techniques for flood volume computation is possible using temperature rainfall and flow rates values